Larvicidal and Adult Mosquito Vector Attractant Activity of Tremella fuciformis Berk Mushroom Extract on Aedes aegypti (L.) and Culex sitiens Wiedemann (Diptera: Culicidae) - Tanawat Chaiphongpachara, Kantima Sumchung, Aegkapun Bumrungsuk, Kitthisak Khlaeo Chansukh (Journal of Applied Pharmaceutical Science, 2018)
In this study, we assessed Tremella fuciformis Berk mushroom extract for larvicidal and adult mosquito attractant activity using Aedes aegypti (L.) and Culex sitiens Wiedemann (Diptera: Culicidae). Five concentrations of extract (120, 12, 1.2, 0.12, and 0.012 mg/L) for larvicidal tests and three concentrations of extract (100, 10, and 1 mg/L) for attraction testing of adult female mosquitoes were used. Results showed no larvicidal activity of T. fuciformis extract against Ae. aegypti larvae and only slight activity against Cx. sitiens larvae, while octenol, tested for comparison, exhibited well larvicidal at the highest concentration (120 mg/L) on Cx. sitiens (19.00 ± 1.00 of 20 killed) fair activity on Ae. aegypti (9.00 ± 1.00 of 20 killed). At 10 mg/L, the T. fuciformis extract attracted the most adults in both species of mosquito, followed by 100 and 1 mg/L, respectively, with Ae. aegypti responding better than Cx. sitiens at all concentrations. At all concentrations, octenol was a significantly (p < 0.05) better attractant than the T. fuciformis extract. As an eco-friendly way to increase the efficiency of mosquito traps, T. fuciformis extract shows potential.
Keywords: Tremella fuciformis mushroom, Aedes aegypti, Culex sitiens, larvicidal effect, mosquito attractant effect.